URGENSI TEORI KONSELING DAN PERSPEKTIFNYA DALAM ISLAM MENJAWAB TUNTUTAN KONSELING RELIGIUS DI MASA DEPAN - Amirah Diniaty (Institut Agama Islam Negeri Imam Bonjol Padang, 2013)
Counseling is a ’multi refential’ science which is developed from several sciences and other theories. In the theoretical perspective, counseling must not be regarded as certain view of providing assistance process, rather, it is a body of knowledge developed from various sources such as the influences of certain techniques, the rise of a status as well as appreciation of subjective individual element, understanding of human’s development and knowledge of society. Counseling process that is not based on theory will mislead councelor and reduce the opportunity to change the client’s behavior. Islam regards counseling as a virtue as many verses of the Quran and Prophet Tradition (Hadith) discuss the practice of counseling. It is important for the counselor to master Islamic teaching approach so that they can fulfil the needs to future religious counseling.